Gas exchange in yellow passion fruit under irrigation water salinity and nitrogen fertilization - José A. C. Wanderley; Carlos A. V. de Azevedo; Marcos E. B. Brito; Fagner N. Ferreira; Mailson A. Cordão; Robson F. de Lima (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objective of this study was to evaluate the gas exchange of ‘Redondo Amarelo’ passion fruit seedlings under the mitigating action of nitrogen fertilization on the salinity of irrigation water. The experiment was carried out in a greenhouse of the Universidade Federal de Campina Grande (CCTA-UFCG), Campus of Pombal, PB, Brazil, The experimental design was in randomized blocks, split plots, comprising five irrigation water electrical conductivities (plot) (ECw) (0.3; 1.0; 1.7; 2.4 and 3.1 dS m-1) and five doses of nitrogen (subplot) (60; 80; 100; 120 and 140% of 300 mg of N dm-3), in five blocks. Plants were grown in pots (Citropote JKS®) with volume of 3.780 mL, filled with soil, bovine manure, wood shavings in a proportion of 2:1:0.5 (mass basis), respectively. Water with salinity levels was applied in the period from 40 to 85 days after sowing. The internal CO2 concentration, transpiration, stomatal conductance and photosynthesis were measured at 55 and 70 days after sowing. There was an attenuating effect of nitrogen doses at irrigation water electrical conductivities of 1.7 and 2.4 dS m-1 on photosynthesis at 55 DAS. Irrigation water salinity reduces most of the variables evaluated, especially at the highest level studied (3.1 dS m-1).